2013
DOI: 10.4236/as.2013.46a003
|View full text |Cite
|
Sign up to set email alerts
|

Soybean meal as a source of protein in formulated diets for tiger grouper, <i>Epinephelus fuscoguttatus</i> juvenile. Part II: Improving diet performances

Abstract: The present study was conducted as a continuation of our previous study on the effects of fish meal replacement with soy bean meal, SBM in the diets of tiger grouper, Epinephelus fuscoguttatus which revealed the possible level of fish meal protein replacement of 30% with positive effect of phytase supplementation in one of the test diet. In the present study, all experimental diets with SBM inclusion (10%, 20%, 30%, 40% replacement levels) were supplemented with phytase and fed to juvenile tiger grouper with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…A study on red sea bream (Pagrus major) showed that the supplementation of 2000 FTU/kg phytase in the soybean meal-based diet showed a significant improvement in the weight gained of fish from 585.3% to 736.2%, feed conversion efficiency from 75.1% to 82.3% compared to fish fed diet without supplementation of phytase (Biswas et al, 2007) and also fulfilled its dietary phosphorus requirement (Laining et al, 2011). Other similar studies were also reported in Nile tilapia fingerlings (Tahoun et al, 2009), rainbow trout juvenile (Oncorhynchus mykiss) (Yang et al, 2010;Castro et al, 2011), gibel carp (Carassius auratus gibelio) (Liu et al, 2011) and tiger grouper (Shapawi et al, 2013b). Besides, higher phytase supplementation of 4000 FTU/kg allowed the use of soybean meal up to 75% in the diet of rainbow trout juvenile with better growth performance and lower nitrogen excretion (Castro et al, 2011).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A study on red sea bream (Pagrus major) showed that the supplementation of 2000 FTU/kg phytase in the soybean meal-based diet showed a significant improvement in the weight gained of fish from 585.3% to 736.2%, feed conversion efficiency from 75.1% to 82.3% compared to fish fed diet without supplementation of phytase (Biswas et al, 2007) and also fulfilled its dietary phosphorus requirement (Laining et al, 2011). Other similar studies were also reported in Nile tilapia fingerlings (Tahoun et al, 2009), rainbow trout juvenile (Oncorhynchus mykiss) (Yang et al, 2010;Castro et al, 2011), gibel carp (Carassius auratus gibelio) (Liu et al, 2011) and tiger grouper (Shapawi et al, 2013b). Besides, higher phytase supplementation of 4000 FTU/kg allowed the use of soybean meal up to 75% in the diet of rainbow trout juvenile with better growth performance and lower nitrogen excretion (Castro et al, 2011).…”
Section: Discussionmentioning
confidence: 63%
“…Many studies had demonstrated the benefits of phytase supplementation in soybean meal-based diet to increase the bioavailability of protein and mineral for better feed efficiency and growth of fish (Biswas et al, 2007;Yang et al, 2010;Laining et al, 2011;Shapawi et al, 2013b). A study on red sea bream (Pagrus major) showed that the supplementation of 2000 FTU/kg phytase in the soybean meal-based diet showed a significant improvement in the weight gained of fish from 585.3% to 736.2%, feed conversion efficiency from 75.1% to 82.3% compared to fish fed diet without supplementation of phytase (Biswas et al, 2007) and also fulfilled its dietary phosphorus requirement (Laining et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made by Debnath et al (2005) who reported improved (p<0.05) crude protein content in Pangasius pangasius. Shapawi et al (2013) also reported significantly improved whole body protein contents in tiger grouper (Epinephelus fuscoguttatus) by the supplementation of 2000 FTU/kg PHY. Contrary to our results, dietary PHY supplementation was not reported to cause any marked improvement in body CP content in rainbow trout (Vielma et al, 1999), Red sea bream (Biswas et al, 2007) and rohu (Xavier et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Which increased its market value, as the fish with less fat contents is tastiest and have high protein contents. In a recent study, Shapawi et al (2013) reported significantly lowered lipid content in tiger grouper having PHY treated diet. Likewise, decreased EE was noticed in P. pangasius and common carp (Rocha et al, 2010) while feeding with PHY treated diets Similarly Pezzato et al (2006) and Furuya et al (2008) reported reduced fat contents in the carcass of Nile tilapia with PHY supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…The poorer GWM utilization compare to the previous study might due to lower digestibility by the less developed digestive system of the smaller juvenile shrimp. Furthermore, larger sizes of organisms were reported to better utilize the plant protein source (Shapawi et al 2013).…”
Section: Discussionmentioning
confidence: 99%